Assessment of toxicity in industrial wastewater treated by biological processes using luminescent bacteria (2016)
ABSTRACT: The toxicity of wastewater from a meat by-products processing company was evaluated before and after treatment using the Sequencing Batch Reactor (SBR). Toxicity tests were carried out by analyzing the inhibitory effect of samples in relation to light emission from marine bacteria of the species Vibrio scheri. The results found that the efluuents prior to treatment were highly toxic (EC50 < 60%) whereas post-treatment results showed low or no toxicity (EC50 > 82%). In some operational stages of the SBR reactor, a high correlation between the ammonia nitrogen present in each sample and the toxicity of wastewater from both the in fluents and the efluents was found, with correlations (R2) of 0.6141 and 0.8158, respectively. As a consequence of these results, the SBR system can be considered ef cient at removing organic matter, and nitrogen, and thereby decreasing toxicity in treated water.